Chronic Constrictive Pericarditis in Association with End-Stage Renal Disease - Roman L. Kleynberg; Vera M. Kleynberg; Leonid M. Kleynberg; Danny Farahmandian (International Journal of Nephrology)
Pericardial involvement in end-stage renal disease (ESRD) is manifested most commonly as acute uremic or dialysis pericarditis and infrequently as chronic constrictive pericarditis (CCP). We report a 27-year-old patient with a history of uncontrolled hypertension, end-stage-renal disease on hemodialysis, who presented with recurrent ascites, dyspnea, and hypotension. After diagnosis with CCP, a partial pericardiectomy was performed; however, the patient did not improve and a salvage total pericardiectomy soon followed. He continued to decompensate and expired following a terminal extubation. No definitive cause of constrictive pericarditis was found. Nonetheless, we surmise it may have developed secondary to his end-stage renal disease. A literature review revealed end-stage kidney disease as a relatively uncommon cause of CCP; only a few other such associations have thus far been reported.